(untitled) (Journal of Informatics Education and Research, 2026)
United Nations Declaration on Rights of the Crime Victim, 1985 and Van Boven/Bassiouni Principles in 2005 were adopted for the justice of crime victims. In line with those international instruments, there have been various institutional developments to protect the rights of crime victims in Nepal. Article 21(2) of the Constitution of Nepal has guaranteed right to compensation of the crime victims as fundamental rights. Crime Victim Protection Act (CVPA), 2018 provides detail guidelines regarding compensation. The UN declaration has recognized Compensation as major victim’s rights and Van Boven/Bassiouni Principles calls for adequate, effective and prompt reparation but it does not seem to be working towards achieving the goal set by the international legal instruments and Nepalese constitution. There is need to reform the law as it’s imperative bring a positive change in the mechanisms of the victim justice system. In absence of such a robust reformation, Nepal’s victim-centric legal framework may not be able to meet the objectives the legislations aim to achieve.